MONITORING OF INTERNET-FACING TECHNOGENIC OBJECTS - D. S. Smoliak; S. N. Petrov; T. A. Pulko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The approach to detection and monitoring of Internet-facing technogenic objects has been described. The method of analysis of public services Shodan and Censys has been proposed. The automation monitoring software has been developed.